PEMENUHAN HAK ISTRI DALAM PERNIKAHAN POLIGAMI SIRRI (Studi Kasus Di Desa Mojotengah Kecamatan Bareng) - Salma Nur Rochma Setya Wardah; Habibi Al Amin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The problem of unregistered polygamous marriages is an interesting issue. Marriages are carried out in accordance with the pillars and conditions, the presence of witnesses and guardians as determined by religion, but are not carried out in the presence of a marriage registrar (PPN). For those who are Muslim, both at the Kua and at the civil registry office for non-Muslims. Many polygamists are carried out only to satisfy their husband's desires. So there is a lack of public knowledge regarding unregistered marriages, especially polygamous unregistered marriages, with the aim of understanding the rights given to polygamists to be fair. This happened to the perpetrators of a polygamous serial marriage in Mojotengah village, Bareng district, Jombang district. Even though they are currently still living together, there are many problems occurring in their families, which is due to unfair factors in providing fair qualities to their wives. For this reason, the aim of this research is to explain the wife's rights in a polygamous serial marriage, and to explain the wife's rights in the complications of Islamic law. This research is qualitative field research with an empirical normative approach. In obtaining data, the author used three data collection techniques, namely interviews, observation and documentation. The author uses data analysis techniques in the form of objective interpretations. Based on the results of research in Mojotengah Village, Bareng District, Jombang, it can be concluded that this alternative requirement is an absolute requirement, meaning that one of the conditions must be present to be able to apply for polygamy. Meanwhile, the cumulative requirements for polygamy are requirements that must be fulfilled in a polygamy application. The rights of wives from sirri polygamy according to Islamic law, the rights of wives emerge from the time the marriage agreement is completed and Islam requires both parents to protect and provide for their children.